5th Wave - Yancey, Richard (New York : G.P. Putnam's Sons, 2013)
"Cassie Sullivan, the survivor of an alien invasion, must rescue her young brother from the enemy with help from a boy who may be one of them"--
Keywords: Extraterrestrial beings; Survival; War; Science fiction; War stories; War stories; Science fiction; Young adult fiction